The Effect of Physical Work Effectiveness and Facilities on Fish Cultivation Satisfaction Through Public Service Quality at The Fisheries Service of West Tanjung Jabung Regency - Umi Masruroh; M. Zahari; Osrita Hapsara (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of work effectiveness and physical work facilities on fish farmer satisfaction through the quality of public services at the Fisheries Service of West Tanjung Jabung Regency. The study used a quantitative approach with an explanatory method. The population in this study was 96 fish farmers receiving services at the Fisheries Service of West Tanjung Jabung Regency, and the entire population was sampled (census method). Data collection was conducted through the distribution of questionnaires compiled based on the indicators of each research variable and measured using a Likert scale. Data analysis was conducted using the Partial Least Squares (PLS) method using a structural model to test the direct and indirect effects between variables. The results showed that work effectiveness and physical work facilities had a positive and significant effect on the quality of public services. Furthermore, the quality of public services had a positive and significant effect on fish farmer satisfaction. Furthermore, work effectiveness and physical work facilities also had an indirect effect on fish farmer satisfaction through the quality of public services as an intervening variable. This study confirms that increasing the work effectiveness of civil servants and providing adequate physical work facilities are important factors in improving the quality of public services and fish farmer satisfaction